Maternal and perinatal outcomes in women with and without hypertensive syndromes submitted to induction of labor with misoprostol - Rossana Mariana Carvalho de Paiva Marques; Alex Sandro Rolland Souza; Francisco Edson de Lucena Feitosa; Aurélio Antônio Ribeiro da Costa; Melania Maria Ramos Amorim (Taylor & Francis Group, 2017)
Objectives: To determine maternal and perinatal outcomes according to the mode of delivery in normotensive and hypertensive women bearing a live, full-term fetus, who were submitted to labor induction with misoprostol. Methods: Retrospective cohort study. The endpoints were tachysystole, uterine hyperstimulation, indications for cesarean section, severe maternal morbidity, side effects, maternal death, 1st/5th minute Apgar, neonatal death, requirement for neonatal intensive care, and birth weight (grams). The chi-square or Fisher's exact test was applied at a significance level of 5%. Risk ratios (RRs) and their 95% confidence intervals (95% CI) were calculated. Results: No significant differences were found in maternal outcome as a function of mode of delivery. First-minute Apgar score <7 was less common with vaginal deliveries in normotensive women (RR = 0.41; 95% CI: 0.18-0.90), this being the only significant difference in perinatal outcome. Conclusion: Maternal and perinatal outcomes were similar in hypertensive and normotensive women submitted to labor induction with misoprostol.